Tree barks as bioindicator for organic and inorganic pollutants : a preliminary study / Muhamad Fares Ameran ... [et al.] - Ameran, Muhamad Fares; Yusoff, Zaini; Masdar, Non Daina; Salmi, Mohamad Dzul Helmee (Universiti Teknologi MARA, Perlis, 2014)
A preliminary study was carried out to investigate the level of air pollution due to anthropogenic (human activities) sources using biomonitoring techniques. Tree barks from six sampling sites near a cement plant in Chuping Perlis were used to detect the level of PAHs and heavy metals emission in the area. Extraction of PAHs and heavy metals was done using Soxhlet extraction and hot block digestion technique respectively. PAHs content was analyzed using Gas Chromatography with Flame Ionization Detector (GC-FID) and compared with six low molecular weight (LMW) single PAHs standards while the heavy metals detection was analyzed by Inductively Coupled Plasma with Mass Spectrometry (ICP-MS). The result showed the presence of all six LMW PAHs with concentration of total PAHs ranging from 3.75 to 22.15 μg/kg. The result from heavy metal determination showed the presence of all the eight targeted elements in the tree bark samples. The concentration of Zn and Cu were found to be among the highest which were 7391.34 μg/kg and 7087.35 μg/kg respectively while Cd gave the lowest concentration at 62.25 μg/kg.